(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2020)
Onomatopoeia is believed to be of a widespread occurrence in all languages of the world though with different extents. Arabic language is attested to be rich in the use of onomatopoeia in speech, prose, and poetry. Omani Arabic, a unique variety of vernacular Arabic spoken in the Sultanate of Oman in the eastsouthern part of Arabia, likewise has numerous usages of onomatopoeic words in everyday life interactions. Both lexical and non-lexical onomatopoeia exist in Omani Arabic falling into three main categories: human sounds, animal sounds, and sounds associated with nature and objects. Onomatopoeic sounds appear in different syllabic forms including full syllables and non-syllabic forms with one or more consonants. The use of voiceless sounds and fricatives is more prevalent compared to other types of sounds. Cases are attested of sounds captured in diverse manners exhibiting alternation among sounds close in place of articulation as well as between emphatic sounds and their non-emphatic counterparts. The use of fricatives is used to mark the duration of sounds as opposed to the use of plosives employed to show abruptness and short duration of sounds. Morphologically, most of these words are used as verbs and derivative nouns. Reduplication is likewise used to mark the intensity and duration of actions signified by these sounds.